Application of Immunohistochemistry in Tumour Classification: A Comparative Study of Canine and Human Tissues - Narad, Ankur; Shukla, Supriya; Sood, Naresh Kumar; Jatav, Gaya Prasad (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
This study was aimed to perform a comparative analysis of canine mammary tumours (CMT) and human breast cancer (HBC) by evaluating  similarities in molecular characteristics and assessing the transmodel potential of CMT for human breast cancer research. Immuno-histochemistry  (IHC) was employed to analyze the expression of key biomarkers, viz., estrogen receptor (ER), progesterone receptor (PR), human epidermal  growth factor receptor 2 (HER-2), and Ki-67 in both canine and human mammary tumour tissues (n=30 each). Tissue samples were processed  using standard IHC protocols, including antigen retrieval, blocking of endogenous peroxidase, and incubation with primary and secondary  antibodies. Biomarker expression levels were quantified and compared across tumour subtypes in both species. The analysis revealed significant  parallels in the expression patterns of ER, PR, HER-2, and Ki-67 between CMT and HBC. Molecular subtypes identified in canines, including luminal  A, luminal B, HER-2 overexpressing, and triple-negative, closely mirrored those classified in human breast cancer. Furthermore, the proliferation  marker Ki-67 exhibited comparable expression across species, suggesting similar tumour growth dynamics. These findings demonstrate that  canine mammary tumours share molecular and histological characteristics with human breast cancer, supporting their value as a translatable  model in breast cancer research. Consequently, canine mammary tumours represent a valuable platform for investigating tumour biology and  therapeutic interventions relevant to human breast cancer.
Keywords: Canine mammary tumours, Comparative oncology, Human breast cancer, Immunohistochemistry, Molecular subtypes